2020
DOI: 10.1053/j.gastro.2020.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Benefit of Achieving Endoscopic and Histologic Remission in Patients With Ulcerative Colitis: A Systematic Review and Meta-Analysis

Abstract: Background & Aims: Clinical remission, defined by a composite of patient reported outcomes and Mayo endoscopy subscore (MES) 0 or 1 is a recommended treatment target in patients with ulcerative colitis (UC). We estimated whether incorporating more rigorous remission definitions, of endoscopic remission (MES 0) and histologic remission, affects risk of relapse.Methods: Through a systematic review, we identified cohort studies in adults with UC in clinical remission that reported a minimum 12-month risk of clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 49 publications
5
68
1
5
Order By: Relevance
“…Our findings do not conflict with Maeda et al, but support that achievement of histologic remission in MES = 1 endoscopic disease provides benefit over and above attaining MES = 1 disease alone. While our findings do suggest that histologic remission may not provide additional benefit in patients who have achieved MES = 0 endoscopic remission, our recent meta‐analysis and systematic review support that histologic remission probably also confers additional benefit over MES = 0 endoscopic remission alone 3 …”
Section: Figurecontrasting
confidence: 67%
“…Our findings do not conflict with Maeda et al, but support that achievement of histologic remission in MES = 1 endoscopic disease provides benefit over and above attaining MES = 1 disease alone. While our findings do suggest that histologic remission may not provide additional benefit in patients who have achieved MES = 0 endoscopic remission, our recent meta‐analysis and systematic review support that histologic remission probably also confers additional benefit over MES = 0 endoscopic remission alone 3 …”
Section: Figurecontrasting
confidence: 67%
“…Histological deep healing is the highest goal of clinical treatment for IBD patients. A recent systematic review and meta-analysis revealed that patients who achieved endoscopic and histological remission have a significantly lower risk of clinical relapse than patients who achieved clinical remission (Yoon et al, 2020). The proinflammatory cytokines levels correlate with the severity of colitis.…”
Section: Discussionmentioning
confidence: 99%
“…For ulcerative colitis, clinical remission determined by rectal bleeding and stool frequency scores along with endoscopic remission were deemed the primary targets, with histological remission an adjunctive goal. The importance of aiming for deeper remission has been reinforced by a greater focus on the accumulation of progressive damage in IBD, 2 as well as evidence showing that even minor endoscopic and histologic abnormalities are associated with poorer subsequent clinical outcomes 3 …”
Section: Figurementioning
confidence: 99%
“…The importance of aiming for deeper remission has been reinforced by a greater focus on the accumulation of progressive damage in IBD, 2 as well as evidence showing that even minor endoscopic and histologic abnormalities are associated with poorer subsequent clinical outcomes. 3 The STRIDE consensus did not recommend the use of fecal biomarkers such as calprotectin as targets in their own right. However, more recent data lends support to the use of non-invasive biomarkers to inform treatment decisions.…”
mentioning
confidence: 99%